Reframing Strategic Alliances as Transformative Strategies for SMEs: An ADO-TCM ‎Integrative Review - Akinson, Akinlemi Omololu; C. R. , Sundara Rajan (International Journal of Accounting and Economics Studies, 2026)
Strategic alliances have become imperative for small and medium-sized enterprises (SMEs) to ‎mitigate the challenges of continuous constraints in resources, innovation, and market growth. ‎However, scholarly research on SME alliances is disjointed and isolated and does not often ‎connect why SMEs enter alliances, how alliances are structured, and what outcomes they ‎provide. This study fills this gap by offering an integrated, theory-informed synthesis of alliance ‎processes in SMEs. The SPAR-4-SLR protocol was used in a systematic literature review (SLR) ‎of 61 peer-reviewed articles published between 2014 and 2025. Data was retrieved from the ‎Scopus and Web of Science databases. The Theory-Context-Method (TCM) in conjunction with ‎the Antecedents-Decisions-Outcomes (ADO) framework was applied in the study, which ‎offered contextual and analytical depth. This review uncovers the multilayered dynamics of SME ‎alliances. SMEs seek alliances for resource access, develop adaptive capacities, venture into ‎digital ecosystems, and pursue sustainable objectives. Strategic decisions range from governance ‎to innovation and knowledge integration. The outcomes extend beyond firm performance to ‎innovation capacity, value creation, internationalization, and sustainability. The literature for the ‎study is, however, dominated by resource-based theory, so also is the methodology adopted by ‎most studies which concentrate on cross-sectional quantitative approaches for most of the ‎studies. This review uniquely bridges the fragmented alliance literature through a coherent TCM-ADO synthesis that explores alliance antecedents, strategic choices, and performance outcomes, ‎advancing an agenda that positions alliances as transformative tools and not compensatory tactics ‎for SME competitiveness in dynamic business environments‎.